2015
DOI: 10.3109/14767058.2015.1012063
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of angiogenic factors, clinical risk factors and uterine artery Doppler for pre-eclampsia and fetal growth restriction in second and third trimester pregnancies in an Ecuadorian population

Abstract: In a high-altitude Ecuadorian population, angiogenic factors and UA PI were useful tools in the prediction of PE and/or FGR. The highest performance was achieved by the combination of these factors, including obstetric and medical history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
(64 reference statements)
1
19
0
1
Order By: Relevance
“…These markers and their ratio are important in clinical monitoring of patients with preeclampsia, and they are used on a regular basis [35][36][37]. The Flt-1/PIGF ratio is increasingly used in the study of restricted intrauterine growth [38]. All these pathological events are associated with hypoxic processes affecting placental vascularisation [19].…”
Section: Discussionmentioning
confidence: 99%
“…These markers and their ratio are important in clinical monitoring of patients with preeclampsia, and they are used on a regular basis [35][36][37]. The Flt-1/PIGF ratio is increasingly used in the study of restricted intrauterine growth [38]. All these pathological events are associated with hypoxic processes affecting placental vascularisation [19].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-six studies (total participants, N = 42,609) were deemed to be eligible for final inclusion. Of these, 21 studies reported the relationship between PlGF and SGA or FGR infants with a participant total of N = 41,837 (10,13,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42), seven studies detailed the predictive value of PlGF for other adverse perinatal outcomes with a participant total of N = 13,401 (8,10,13,14,25,38,43) and three studies described the role of PlGF in distinguishing between placentally-mediated FGR and constitutionally SGA infants with a participant total of N = 841 (10,44,45). Table 1 and include the type of study, populations of recruited women, total number of participants, gestation at which PlGF was measured, type of PlGF assay, criteria for abnormal maternal PlGF levels if defined and specific outcomes investigated.…”
Section: Study Selectionmentioning
confidence: 99%
“…[65] [66] It is combined with measurements of the middle cerebral artery systolic/diastolic ratio, resistance index and pulsatility index. High uterine artery pulsatility index > 0.58 may be considered abnormal.…”
Section: Diagnosis Of Pre-eclampsiamentioning
confidence: 99%